KARAKTERISTIK KOMPOSIT ASPAL KARBOSIL DARI LIMBAH SEKAM PADI - liyana mardova; Simon Sembiring; Junaidi Junaidi (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
In this study, the characterization of the carbosil asphalt composite was carried out with a composition variation of 1:9; 1.5:8.5; 2:8; 2.5:7.5; 3:7 and the ratio for pure carbosil without the addition of asphalt. Carbosil is obtained from rice husk waste by using the pyrolysis method. This research was conducted to determine the effect of temperature on the microstructure, structure and functional groups of carbosil asphalt composites. XRD analysis obtained that the phase formed from each composition variation was an amorphous phase. The DTA/TGA analysis shows that there is a change in energy due to the addition of heat, which is indicated by the presence of mass shrinkage in the sample. Compressive strength results indicate that the strength of the carbosil asphalt composite with different material compositions affects the resistance to cracking.